Need for structured healthcare organization and support for return to work after stroke in Sweden: Experiences of stroke survivors - Gunvor Gard; Hélène Pessah-Rasmussen; Christina Brogårdh; Åsa Nilsson; Ingrid Lindgren (Medical Journals Sweden, 2019)
Objective: To explore stroke survivors' experiences of healthcare-related facilitators and barriers concerning return to work after stroke. Design: A qualitative study. Setting: Outpatient stroke rehabilitation unit at a University Hospital in southern Sweden. Participants: A convenient sample of 20 persons admitted to Skåne University Hospital for acute stroke care (median age 52 years), in employment of at least 10 h per week at stroke onset and having been referred to stroke rehabilitation within 180 days. Methods: The interviews were performed by focus groups, and the data were analysed by content analysis. Results: Facilitating factors were a tailored rehabilitation content with relevant treatments, adequate timing and a structured stepwise return-to-work process. A lack of sufficient early healthcare information, rehabilitation planning and coordination were perceived as barriers. An early rehabilitation plan, a contact person, and improved communication between rehabilitation actors were requested, as well as help with work transport, home care, children and psychosocial support for families. Conclusion: Tailored rehabilitation content and a structured stepwise return-to-work process facilitated return to work. Insufficient structure within the healthcare system and lack of support in daily life were perceived barriers to return to work, and need to be improved. These aspects should be considered in the return-to-work process after stroke.